Sistem Pendukung Keputusan Pemilihan Pelanggan Terbaik Menggunakan Metode SD-MOORA - Yuri Rahmanto (PT. Tech Cart Press, 2024)
Selecting the best customer is an important process in business that aims to recognize high-value customers for the company based on factors such as purchase frequency, transaction value, loyalty, and long-term business potential. However, this process often faces challenges, especially when it comes to objective and consistent measurements. One of the main problems is the complex and dynamic variation of customer data, making it difficult for companies to determine the right metrics to comprehensively assess customers. SPK for selecting the best customers using the SD-MOORA method is a system designed to assist companies in evaluating and selecting the best customers based on various criteria. With the SD-MOORA method, the system can automatically consider changes in data or variability between criteria, making the evaluation process more dynamic and adaptive to data fluctuations. The results of the ranking of the best customers using the SD-MOORA method, Customer 8 occupies the first position with the highest optimization value of 0.39079, followed by Customer 4 who obtained a score of 0.3734. Furthermore, Customer 2 is in third place with a value of 0.35515. These results show that Customer 8 is the best based on optimization value, while Customer 5 is ranked at the bottom.